Determination of explosion parameters of hydrogen-air mixtures in closed vessel - Norita, Abu Kori (2013)
Hydrogen has been proposed as a potential fuel to replace fossil fuels in consideration to reduce carbon emissions. This paper presents experimental data on the characteristics of hydrogen-air explosion in air mixture using 20-L sphere. This data includes the maximum explosion pressure, deflagration index, and the maximum rate of pressure rise. Methods and equations are available to estimate these parameters. The experimental maximum explosion pressure agrees with the theoretical value estimated using a chemical equilibrium program if the concentration of hydrogen is from 10 % to 75% in air but not close to the flammable limits. Therefore, the maximum pressure can be estimated conventionally by the equilibrium program regardless of the size of the explosion vessel. Deflagration index for mixture of hydrogen in air, even if normalized by the cube root of the number of vessels explosion, is shown to be sensitive to the vessel volume. The fraction of burnt gas just before the flame contacts the wall has a dominant effect on the deflagration index (Crowl, 2001). From experimental data the deflagration index of hydrogen explosion in 20 L is 212.54 bar.m / sec. The maximum explosion pressure is 2.8 bar at the amount of 22% hydrogen in air and the maximum rate of increase in pressure is 783 bar. Experimental values are different from the theoretical value because there is an error during the experiment run. So, improvements need to be done to get better data experimental procedures in the future.